Optimal tuning of fractional‐order proportional, integral, derivative and tilt‐integral‐derivative based power system stabilizers using Runge Kutta optimizer - El‐Dabah, Mahmoud Abbas; Kamel, Salah; Abido, Mohammad Ali Yousef; Khan, Baseem (Engineering reports (Hoboken, N.J.), 2022)
Low‐frequency power system oscillation is of great concern as it may lead to power system instability. Moreover, this action will lead to the abate capability of electric power transfer. By introducing a stabilizing signal into the excitation system, it was possible to improve the damping in the system. The power system stabilizer (PSS) provides this signal. This manuscript aims to find the optimal tuning of three different PSS controllers using a recent optimization algorithm called Runge Kutta optimizer (RUN). Based on the obtained results, the RUN shows superiority and fast convergence over competitive algorithms. In addition, the fractional‐order proportional, integral, derivative (FOPID) and tilt‐integral‐derivative (TID) based PSS shows great damping capability over the lead–lag, PI, and FOPID‐based PSS. Also, the TID‐based PSS achieves better performance indices in terms of the lowest maximum overshoot and minimum settling time. Hence, it is recommended for PSS based controller. This article aims to the optimal tuning of three types of PSS using a recent optimization algorithm called Runge Kutta.